Fingolimod (FTY-720) is Capable of Reversing Tumor Necrosis Factor Induced Decreases in Cochlear Blood Flow. Issue 8 (September 2017) - Bertlich, Mattis; Ihler, Friedrich; Weiss, Bernhard G.; Freytag, Saskia; Jakob, Mark; Strupp, Michael; Pellkofer, Hannah; Canis, Martin
Abstract : Hypothesis: The potential of Fingolimod (FTY-720), a sphingosine-1-phosphate analogue, to revoke the changes in cochlear blood flow induced by tumor necrosis factor (TNF) was investigated. Background: Impairment of cochlear blood flow has often been considered as the common final pathway of various inner ear pathologies. TNF, an ubiquitous cytokine, plays a major role in these pathologies, reducing cochlear blood flow via sphingosine-1-phosphate-signaling. Methods: Fifteen Dunkin-Hartley guinea pigs were randomly assigned to one of three groups (placebo/placebo, TNF/placebo, TNF/FTY-720). Cochlear microcirculation was quantified over 60 minutes by in vivo fluorescence microscopy before and after topical application of placebo or TNF (5 ng/ml) and after subsequent application of placebo or FTY-720 (200 μg/ml). Results: Treatment with TNF led to a significant decrease of cochlear blood flow. Following this, application of placebo caused no significant changes while application of FTY-720 caused a significant rise in cochlear blood flow. Conclusions: FTY-720 is capable of reversing changes in cochlear blood flow induced by application of TNF. This makes FTY-720 a valid candidate for potential treatment of numerous inner ear pathologies. Abstract : Supplemental Digital Content is available in the text